Controlling functions of hydrothermal activity to shale gas content-taking lower Cambrian in Xiuwu Basin as an example. (August 2017) - Zhang, Kun; Jiang, Zhenxue; Yin, Lishi; Gao, Zhiye; Wang, Pengfei; Song, Yan; Jia, Chengzao; Liu, Weiwei; Liu, Tianlin; Xie, Xuelian; Li, Yirun
Abstract: Lower Cambrian is the main target intervals of marine shale gas exploration and exploitation in China. Shale gas bearing varies greatly among different intervals and how to determine favorable targets is an important problem to be solved. In this article, taking Jiangye-1 well in Xiuwu Basin as an example, according to core description, logging data analysis, section authentication, mineral and elemental composition analysis, bulk and effective porosity tests, total organic carbon (TOC) and gas content tests, lower Cambrian Wangyinpu and Guanyintang formations have been studied. Results show that TOC content is the dominating factors for effective porosity and gas bearing content, redox conditions and bioproductivity control the enrichment of sedimentary organic matter. The water reducibility of SQ1 varies greatly, of SQ2 and SQ3 is generally strong, reducibility of all the three sequences is stronger than those of SQ4 and SQ5; the bioproductivity of SQ3 is the highest and little difference in the bioproductivity has been found between SQ1 and SQ2, both of which show higher values than SQ4 and SQ5. Except for terrigenous siliceous minerals, large amounts of hydrothermal origin siliceous minerals exist in lower Cambrian Wangyinpu and Guanyintang formations. Specifically, siliceous origin of SQ1 varies greatly, part of intervals are terrigeneous origin and part of intervals are hydrothermal origin; most siliceous minerals of SQ2 and SQ3 are hydrothermal origin, whose content takes up 10%–30%; compared with SQ2 and SQ3, content of hydrothermal origin siliceous minerals drops in SQ4 and terrigeneous siliceous content increases; siliceous minerals of SQ5 originate from normal terrigeneous clastic deposition. Hydrothermal activities are helpful for the increase of reducibility of seawater and enhancing bioproductivity, the sedimentary organic matter abundance is thus controlled and the enrichment of shale gas is further affected. Hydrothermal activities are generally developed in the early Cambrian in South China. The intervals deposited when frequent hydrothermal activities occurred are exactly favorable targets of shale gas in lower Cambrian. Highlights: Vertical heterogeneity of studied shale has been characterized within sequence stratigraphy. Genesis of siliceous mineral contents of each sequence in the lower Cambrian has been determined. Effects of hydrothermal activity to the enrichment of sedimentary organic matter has been illuminated. Control functions of shale gas-bearing performed by hydrothermal activity has been expounded.